Komparasi Penggunaan Tindak Tutur Direktif Dalam Buku Teks Bahasa Indonesia Ktsp Jenjang Sekolah Menengah Pertama - Rafika Sari, Lina, Laili Etika Rahmawati, S.Pd., M.Pd (2017)
Behavior acting certainly have a relationship with the presence of speakers and partners said. Directive speech act will always involve speakers and opponents he said. If the speech tangible form of writing then indirectly involves the author and reader. Interesting issues to be studied can be formulated, namely first how the form of speech act directive in textbook of Indonesian language class 7 junior high school? Secondly how is the difference between the use of the directive utterance in the 7th grade textbook of Indonesian junior high school ?. The purpose of this research include first digging the form of directive speech acts in BTBI KTSP junior high school level, second Describe the difference of speech acting use directive in BTBI KTSP junior high school level in class 7. The method used in this research is by qualitative method description description with Data analysis techniques using content analysis and data collection with data collection techniques with technical study documentation. The result of this research data analysis is to produce the data of the directive which is classified into three types, namely the directive affixed -kan, the particle directive -lah, the speech of the directive affixed -kan and particles -lah, and the difference of the use of the particle-directive directive and - Is very influential in its use.